Pengaruh Investasi Dalam Negeri, Pendidikan, dan Pengangguran Terhadap Ketimpangan Pendapatan di Indonesia - Rosalia Mumtaz; Amar, Syamsul (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to identify the impact of various factors on income inequality in Indonesia. These factors include (1) domestic investment, (2) education, (3) unemployment rate, (4) domestic investment, education, and unemployment on income inequality in Indonesia. This study uses a quantitative approach by utilizing secondary data in the form of panel data, which combines time series data from 2013 to 2022 with cross-section data from 34 provinces in Indonesia. This study uses panel data analysis. The results show that domestic investment has an insignificant effect while education and unemployment rate have a significant negative effect on income inequality.